(untitled) (Proceedings of International Educators Conference, 2024)
Globally, the proportion of older people aged 65 years and over continues to increase (5). According to UN statistics, in 2019, the elderly population aged 65 years and over accounted for 9% of the total population, and this proportion is projected to increase to 16% by 2050 and exceed 23% by 2100 (3,6). Age is a major risk factor for the development of chronic diseases, and more than 50% of older adults suffer from at least one type of chronic disease (2,4). These chronic diseases pose a significant healthcare burden that will become even worse in the future (1,7). Therefore, it is advisable to prevent the occurrence of these diseases as early as possible.